Konstruksi dan Implementasi Pendidikan Agama Islam Berbasis Pembinaan Akhlak di Lembaga Pendidikan Formal - Roihan, Muhammad (Hikmah, 2023)
Morals are the essence of Islamic education, teaching Islamic education means teaching morals. This is what is done in madrasas, but of course the construction and implementation are not the same as one another. With regard to that, this research aims to analyze the construction and implementation of Islamic religious education in fostering students' morals. This research was conducted at MAN 2 Medan. The research method used is a qualitative approach, where the data sources used consist of primary data sources and secondary data. Data collection methods in this writing are observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The results of the writing indicate that; 1) the implementation of Islamic religious education learning in fostering the morals of students at MAN Medan is carried out in three ways, namely learning in the form of giving material, exemplary and habituation. The material taught is directly related to the moral development of students 2) the moral development of students must continue to be developed by increasing and strengthening discipline in implementation. 3) as for the factors that hinder Islamic religious education learning in fostering the morals of students, namely the time of implementing learning and the environment, because teachers must provide reinforcement about learning material in every lesson and increase supervision so that students do not do things that violate the rules..